THE INFLUENCE OF CUSTOMER EXPERIENCE AND BRAND TRUST ON PURCHASE INTENTION OF AZARINE BRAND IN PULO GADUNG - Safitry, Sakinah Yulya; Herawaty, Heny (Kinerja, 2025)
This research aims to determine the effect of customer experience and brand trust on purchase intention for Azarine products. The study used a sample of 110 respondents. Data collection techniques involved a questionnaire consisting of 30 items rated on a Likert scale (1-5), which were tested for validity and reliability. The research employed classical assumption tests, including normality test, multicollinearity test, and heteroscedasticity test. The analysis methods used were multiple regression analysis, multiple correlation, coefficient of determination, and t test. Based on the results of the coefficient of determination (R²) among customer experience (X1), brand trust (X2), and purchase intention (Y), the findings indicate that customer experience has a positive and significant effect on purchase intention with a value of (8.483 > 1.982) and a significance value of 0.000 < 0.05, thus rejecting Ho and accepting Ha. Meanwhile, brand trust does not have a significant effect on the purchase intention variable with a value of (0.404 < 1.982) and a significance value of 0.687 > 0.05, thus accepting Ho and rejecting Ha.